The severity of preeclampsia and its associated factors in Hospital Universiti Sains Malaysia - Mat Tamizi, Nurdiyana Farhana (2017)
Background: Preeclampsia (PE) is one of the leading cause of maternal mortality and morbidity worldwide. It occurs after 20 weeks of gestation with the presence of hypertension and proteinuria. The aim of this study was to determine the proportion and the associated factors of PE according to its severity among patients in Hospital USM. Methods: A cross-sectional study involving 200 patients diagnosed with PE between years of 2011 to 2016 who were followed up and delivered in Hospital USM were included in this study. Patients from other referral hospitals in Kelantan and nearer states were also included to be the study samples. We also include those of chronic hypertension with superimposed PE, hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome, and eclampsia. The severity classification of mild, moderate and severe PE was determined based on the National Institute of Health and Care Excellence (NICE) guideline. Ordinal logistic regression was used for analyzing. Results: The percentage of PE among patients in Hospital USM were found to be 34.7% in mild, 30.2% in moderate and 35.1% in severe cases. Higher uric acid resulted in greater odds of getting severe versus mild PE (Adjusted odds ratio (OR): 1.05, 95% CI: 1.02, 1.07) after adjusted for other variables. Patients having chronic hypertension (Adjusted OR: 2.36, 95% CI: 1.28, 4.33) and gestational diabetes mellitus (GDM) (Adjusted OR: 0.53, 95% CI: 0.30, 0.96) were also found to be associated with the severity of PE. Conclusion: Those who developedmild and severe PE was higher compared to moderate PE in this population. Patients with high uric acid and chronic hypertension have higher chances to get severe PE, while those with GDM was more likely to have mild PE. Uric acid, chronic hypertension, and GDM were significantly found to be associated with the severity of PE among patients in Hospital USM. A routine screening for PE based on BP and urine protein measurement should be practiced and done at every antenatal visit as recommended by World Health Organization (WHO).